Épistémologie de la turcologie - Emmanuel Szurek (European Journal of Turkish Studies)
The term Turcology refers to practices that are so diversified that it is doubtful whether they can be referred to via a single epistemological architecture. Conversely, a variety of scholarly designations (‘Turkology’, ‘Turkic studies’, ‘Turkish studies’, ‘science of Turkishness’, ‘study of Turkey’) are available on the international linguistic marketplace to denote this body of studies. In this essay, we intend to explore the question of tension between Turkey, understood as a national construction and a state formation, and Turcology, conceived as a theoretical and practical modality of scholarly investigation. The article will shed light on two matters: the first, philological, will consist in dissecting a few core concepts and names of Turcology in their temporal and spatial variability; the second, historiographical, will outline how the history of the field is written and why the different patterns that shape its narrative (nativism, Eurocentrism, millennialism) tell more about the so-called Turcologists than about Turcology itself.